Extruded snack elaboration from cereals and giant squid protein concentrate (Dosidicus gigas) and determination of its shelf life - Espinoza C., Karina (2021)
The objective was to obtain a snack extruded from cereals (corn, rice, kiwicha) and giant squid protein concentrate (CPCG), which meets the protein and amino acid requirements for children aged 5 to 12 years. The process flow was reception of the raw material, ground, weighed and mixed, conditioning the mixture, extruded, cooled, packed in a bioriented polypropylene bag, sealed and stored. The base mix included: 60.0% corn, 18.5% rice, 15.0% kiwicha and 4.0% CPCG. Likewise, the suitable parameters for the extrusion process were: 12.6% moisture of the mixture and screw speed of the extruder of 150 RPM. The extruded snack had a round shape with an average diameter of 1,3 cm, cream color and no smell and taste of the giant squid resource. The expansion index was 3.3 and the apparent density was 66.76 g/L. Its chemical composition was 16.8% protein, 5.35% moisture, 1.89% fat, 1.05% fiber, 2.01% ash, and 72.91% carbohydrates. The extruded snack presented microbiological values in accordance with those required by RM N°591-2008/MINSA. Its shelf life, determined by Accelerated Testing, was 15 weeks. Nutritionally, the extruded snack can be used for children.